Korelasi Aktivitas Fisik dengan Kadar Vitamin D pada Kelompok Lanjut Usia - Lontoh, Susy Olivia; Firmansyah, Yohanes; Santoso, Alexander Halim; Destra, Edwin; Gunaidi, Farell Christian; Alvianto, Fidelia (Pusat riset dan Inovasi Nasional, 2025)
Elderly individuals often experience physiological and health-related changes, including reduced muscle quality and decreased levels of physical activity. This decline negatively impacts overall health, increases the risk of chronic diseases, and diminishes the ability to perform daily activities. This study aimed to examine the relationship between vitamin D levels and physical activity in older adults. A cross-sectional study was conducted at the Bina Bhakti Nursing Home involving 93 participants aged 60 years and above. Physical activity was assessed using the International Physical Activity Questionnaire (IPAQ), while vitamin D levels were measured through venous blood sampling. Statistical analyses included descriptive statistics and Spearman correlation. The average age of the participants was 74.34 years, with a mean vitamin D level of 23.73 ng/mL. Based on IPAQ results, 26.9% of participants had low physical activity, 44.1% moderate, and 29% high. Spearman correlation revealed a weak but statistically significant positive correlation between vitamin D levels and physical activity (r = 0.240, p = 0.021). These findings suggest that higher physical activity levels are associated with higher vitamin D concentrations. Engaging in outdoor activities that promote sun exposure and an active lifestyle contributes to maintaining adequate vitamin D levels, which are essential for muscle function, balance, and bone health. Therefore, ensuring sufficient vitamin D status is crucial for supporting optimal physical activity and enhancing the overall health and quality of life among the elderly.